Method of data interleaving for H.264 video communication - SONG Bin; GUO Chun-fang; QIN Hao (Tongxin xuebao)
According to the NALU of H.264 and the characteristic of real-time video communication,a method of data interleaving for H.264 video communication was presented.Using forward erasure correction,this method could provide the unequal protection mechanism to the H.264 video stream.The more important the H.264 video stream,the stronger protection it could provide.Furthermore,a novel format of RTP payload and encapsulation was also proposed.Simulation results show that the quality of the reconstructed video can be greatly increased with similar bit rates by using the presented method.